Forest cover drives leaf litter ant diversity in primary rainforest remnants within human-modified tropical landscapes - Ahuatzin, Diana A. (2019)
The main effects of habitat loss and fragmentation have been addressed through changes in diversity patterns at different spatial levels. Species richness and diversity are the most used descriptors to assess the effect of changes in land use on tropical communities. However, other biological responses such as richness and diversity of trophic guilds may also provide a better understanding about the robustness and resilience of tropical environments to disturbance. In this study, we evaluated how changes in local and landscape characteristics associated to habitat loss and fragmentation affect: (i) species richness and Shannon diversity as well as (ii) trophic guild richness and diversity of leaf litter ants in human-modified tropical rainforest landscapes in Mexico. For this, we sampled ants in 16 sampling sites and recorded a series of descriptors at both local (i.e. elevation, temperature, relative humidity, soil pH, canopy cover, litter volume and vegetation structure) and landscape level (i.e. landscape heterogeneity, forest cover and connectivity). Overall, we observed that increasing primary forest cover within the sampling sites positively influenced richness and diversity of species and trophic guilds. In addition, at the local level, we found that only richness and diversity of ant species were negatively associated with tree density (i.e. number of trees, litter volume and canopy cover). These findings suggest that opportunistic species can be favored in environments with low tree density. In short, our complementary approach highlights the importance of environmental variability and primary forest cover in the maintenance of ant biodiversity in primary rainforest remnants.